PELATIHAN PEMBUATAN KEMASAN (PACKAGING) PADA UMKM KERUPUK BAWANG DI DUSUN GUNUNG WIJIL, DESA GUBUG, KECAMATAN CEPOGO, KABUPATEN BOYOLALI - DEWI AGUSTINA; TEGAR HARBRIYANA PUTRA (KRIDA CENDEKIA, 2022)
Training on the packaging production of “Kerupuk Bawang” aims to provide insight into the design and form of new packaging to increase the product’s value and safety. The methods applied in this activity are training on packaging design and labeling of packages, the demonstration method on the label design process and the practice method which allow the participants to have direct experience in making the packaging of “Kerupuk Bawang”. The assessment method is by observing the results created, from the results showed that relatively significant skills and abilities to produce packaging products, so it can be concluded that this activity has succeeded in improving the ability of the participants. In addition, the performance and participation of the participants were also reviewed. At the end, the activity is beneficial to increase the quality of processed products.